2014
DOI: 10.4028/www.scientific.net/amr.971-973.1529
|View full text |Cite
|
Sign up to set email alerts
|

An Edge Detection Method Based on Improved Sobel Operator

Abstract: The edge detection which comes from the classical Sobel operator in the image is based on the horizontal gradient and vertical gradient direction. On the basis of the template from two directions the method which is to detect the edges of eight directions is discussed in this paper. The image edge detection based on multiple directions can improve the accuracy of edge detection. The numerical experimental results show that the proposed method can get the smooth, continuous, multiple directions edges, and can r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…There is a thermal image in figure 6(a), which is captured by microwave thermography when detecting an absorbing coating with a rectangular defect. In addition, the image has been processed by classical operators such as Sobel [19][20][21] and Canny [22][23][24], and the obtained results are shown in figures 6(b) and (c). It is found that defect features obtained by these operators are roughly similar to the actual rectangular defect, but the edge lines are very rough.…”
Section: Image Algorithm For Defect Recognitionmentioning
confidence: 99%
“…There is a thermal image in figure 6(a), which is captured by microwave thermography when detecting an absorbing coating with a rectangular defect. In addition, the image has been processed by classical operators such as Sobel [19][20][21] and Canny [22][23][24], and the obtained results are shown in figures 6(b) and (c). It is found that defect features obtained by these operators are roughly similar to the actual rectangular defect, but the edge lines are very rough.…”
Section: Image Algorithm For Defect Recognitionmentioning
confidence: 99%
“…In 2012, HE et al [7] improved the traditional Sobel operator detection algorithm. In 2014, SUN et al [1] expanded the Sobel operator into eight directions. In 2016, SHI et al [8] Journal of Signal and Information Processing added 6 templates with different directions to Sobel operator.…”
Section: Sobel Edge Detection Operatormentioning
confidence: 99%
“…Edge is one of the most basic and important features of an image. In a digital image, edge refers to the collection of pixels with a step-change in the greyscale of surrounding pixels, which exists in the target and background, target and target, region and region, elements and elements [1]. So, the essence of image edge detection is to detect the change of position feature in the image.…”
Section: Introductionmentioning
confidence: 99%
“…The edge detection is realized by differentiating the gray value of the image with differential operator. Sobel operator in [7] and Canny operator in [8] are commonly used differential operators for image edge detection, which are widely used in image edge extraction. In most cases, image segmentation and image edge extraction are achieved via converting a color image into a grayscale image.…”
Section: Improved Parameter Kernel Map Cutting Algorithmmentioning
confidence: 99%